Необычная подвеска с городища Супруты - Мурашёва, В.В. (Хазарский альманах, 2020)
The article is devoted to the publication of a pendant with an uncertain image found on the settlement of Supruty (IX – beginning of Xth centuries in Tula region). Features of the material culture of this site, due both to its location on the border of spheres of infl uence of the Varangians and the Khazars (in the Oka basin), and the entry into the system of the Don River Route. The key to deciphering the image is a belt plaque depicting a winged dog – Senmurv from a private collection originating from the North Caucasus. Such a plaque served as a model for the manufacture of Supruty pendant. The meaning of the image was misunderstood by the master who made the decoration. The pendant is part of the block of “eastern” products from Supruty, the site with the main Slavic (Romny culture) population.